The association between oxidative balance scores and all-cause mortality and cancer-specific mortality in cancer survivors: a retrospective cohort study - He, Ran; Zhu, Qilei; Ye, Youjun; Tu, Qingyu; Yang, Jiayao; Chen, Shuaihang; Liu, Qiannan; Xie, Changsheng (Frontiers in Nutrition, 2025)
BackgroundNumerous studies have established that oxidative stress significantly affects the long-term survival of cancer survivors. However, there is currently no comprehensive measure to assess oxidative stress levels in these individuals that associates with all-cause, cause-specific, and cardiovascular disease (CVD) mortality. This study aims to investigate the relationship between Oxidative Balance Score (OBS) in American cancer survivors and their risks of all-cause, cancer-specific, and CVD mortality.MethodsThis research included cancer survivors from the National Health and Nutrition Examination Survey dataset covering the 2001–2018 cycles, incorporating appropriate weighting. The OBS, a composite index reflecting oxidative stress status, was constructed based on 16 dietary components and 4 lifestyle factors, with higher OBS indicating greater antioxidant capacity. Using multivariable Cox regression, restricted cubic splines analysis (RCS), subgroup analysis, and sensitivity analysis, we examined the associations between OBS and all-cause, cancer-specific, and CVD mortality, including further stratified analyses for specific cancer types and populations.ResultsThe study enrolled 2,131 eligible cancer survivors, with a median follow-up of 115 months and 673 recorded deaths. Weighted multivariable Cox regression results showed that each unit increase in OBS was associated with a 3% decrease in all-cause mortality (Hazard Ratios [HR]: 0.97, 95% Confidence interval [CI]: 0.95, 0.99, p = 0.006). Among participants, those in the highest OBS quartile (Q4) had a 40% lower risk of all-cause mortality compared to those in the lowest quartile (Q1) (HR: 0.60, 95% CI: 0.41, 0.88, p = 0.009). A similar significant association was found with cancer-specific mortality, while no significant association was noted for CVD mortality. RCS analysis further highlighted a significant linear negative association. Subgroup analyses indicated stronger associations with all-cause and cancer-specific mortality among breast cancer patients, those without stroke or arthritis individuals. Sensitivity analysis confirmed the robustness of these findings.ConclusionThe study reveals a significant linear negative association between OBS in cancer survivors and both all-cause and cancer-specific mortality.